The effectiveness of high-dose inhaled budesonide therapy in the treatment of acute asthma exacerbations in children - (:unkn) unknown (My University, 2001)
BACKGROUND: International guidelines recommend the use of systemic steroids for the treatment of acute asthma attack if it has not been resolved within 24 to 36 hours of home management with regular beta2 mimetic inhalation. Such therapy for infrequent exacerbations is unlikely to have serious systemic effects. Unfortunately, many patients receiving frequent courses are potentially at risk for corticosteroid-induced side effects such as adrenal suppression, depression of linear growth, and osteoporosis. OBJECTIVE: To decrease the use of frequent oral corticosteroid courses in children, this study was designed to evaluate the efficacy of high-dose inhaled steroids in comparison with oral steroids, in the therapy of acute asthma exacerbations in children. METHODS: Sixty children who have experienced an acute exacerbation of asthma unresponsive to home management with regular use of inhaled beta2 mimetics, yet not severe enough to hospitalize, were randomized to be treated with either high-dose inhaled budesonide (1,600 microg daily) or oral methylprednisolone (1 mg/kg daily) plus medium-dose inhaled budesonide (800 microg daily, both in addition to inhaled terbutaline, 2,000 microg daily). Pre- and posttreatment pulmonary index scores, forced expiratory volume in one second (FEV1), forced vital capacity (FVC), FEV1/FVC and forced expiratory flow 25% to 75% (FEF25%-75%) were evaluated. RESULTS: The mean number of decrease in pulmonary index score was 2.61 +/- 1.12 in the high-dose budesonide-receiving group (group I) and 1.90 +/- 1.08 in the oral steroid-receiving group (group II). There was a statistically significant difference between the two groups, in favor of group I (P = .038). No statistically significant difference was detected between the two groups with respect to the increase in lung function test measurements (FEV1, FEV1/FVC, FEF25%-75%; P = .790, .959, .819, respectively). CONCLUSIONS: Short-term high-dose budesonide therapy can be considered an alternative for children who are experiencing an acute asthma attack that is unresponsive to home management with regular use of an inhaled beta2 mimetic, yet who are not severe enough to hospitalize.
Keywords: Female; Humans; Male; Child; Administration, Oral; Anti-Inflammatory Agents; Acute Disease; Administration, Inhalation; Asthma; Budesonide; Respiratory Function Tests; Methylprednisolone; Sympathomimetics; Terbutaline